Níveis de ADAM10 no líquido cefalorraquidiano e soro de indivíduos com doença de Alzheimer - Peron, Rafaela Cardoso (2018)
Researchers have pointed out that the identification of ADAM10 as a biomarker can be an important tool to aid in the clinical diagnosis of AD. The proposal of ADAM10 as a biomarker occurs because it is involved in different physiological and pathological processes, including AD. Studies indicate that ADAM10 platelet levels are lower in patients with AD compared to healthy subjects, however, there are few studies on the expression and activity of this protein in cerebrospinal fluid (CSF). This study was based on the hypothesis that levels of inactive ADAM10 in CSF and serum are increased in AD compared to cognitively healthy subjects. We evaluated levels and activity of ADAM10 in CSF and serum of patients with AD dementia and mild neurocognitive disorder (TNCL). The participants were submitted to clinical and neurological evaluations, and later CSF and serum samples were collected. The data obtained were analyzed in a database to perform descriptive statistical analyzes, considering statistical significance of 5% (p <0.05). It was possible to demonstrate that levels of soluble ADAM10 are elevated in the CSF and blood serum of patients with AD. Enzyme assays demonstrated absence of ADAM10 activity in serum and CSF, with the presence of ADAM10 activity in platelets. These results allow us to conclude that increased levels of ADAM10 in CSF and serum correspond to the inactive protein and strengthen ADAM10 as a biomarker for AD.